GAMBARAN KESEPIAN PADA ANAK TUNGGAL - Devi Jatmika; Dina Argitha (Psibernetika, 2013)
Nowadays, one child families have become a popular phenomenon in many countries, especially in Western countries and China with its one-child policy. Based on birth order literature and research, only children were perceived with negative stereotype among society. Only children were described as lonely, selfish, and dependent. A qualitative study with phenomenological analysis was held in order to describe and understand the loneliness state of only children. The participants were two only teenagers around the age 18-22 years old. Intra-analysis and inter-analysis were conducted. The results showed that the two participants had different state of loneliness. Keywords: Loneliness, the only child